Existence of mild solutions for nonlocal perturbed evolution equations with infinite state-dependent delay in Fréchet spaces - Selma Baghli-Bendimerad; Imane Abibssi (Archives of Control Sciences)
In this work, we give sufficient conditions to get the existence of mild solutions for two classes of first-order semilinear functional and neutral functional perturbed evolution equations with infinite state-dependent delay when the conditions are nonlocal using Avramescu nonlinear alternative for the sum of compact operators and contraction maps in Fréchet spaces, combined with semigroup theory.